1975
DOI: 10.1007/bf01352587
|View full text |Cite
|
Sign up to set email alerts
|

Study of the 4471 � and 4922 � lines in the afterglow of an helium plasma produced by laser

Abstract: We address the problem of the definition of the finite-volume correlation length. First, we study the large-N limit of the N -vector model, and we show the existence of several constraints on the definition if regularity of the finite-size scaling functions and correct anomalous behaviour above the upper critical dimension are required. Then, we study in detail a model in which the zero mode in prohibited. Such a model is a generalization of the fixed-magnetization Ising model which is equivalent to the lattic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1975
1975
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…12, reinforces the reliability of using this parameter as a mean to obtain the electron density in the plasma. As can be seen in that figure, simulation results for a pure He plasma in thermodynamical equilibrium and different electron temperatures have been compared to results from different experiments (Nelson & Barnard 1971;Baravian et al 1975;Diatta et al 1976;Adler & Piel 1991;Pérez et al 1996) and a general good agreement is found. As happened before in other comparisons, the worst agreement corresponds to the comparison with the results of Nelson & Barnard (1971) and Baravian et al (1975).…”
Section: Distance Between the Allowed And The Forbidden Componentsmentioning
confidence: 66%
See 2 more Smart Citations
“…12, reinforces the reliability of using this parameter as a mean to obtain the electron density in the plasma. As can be seen in that figure, simulation results for a pure He plasma in thermodynamical equilibrium and different electron temperatures have been compared to results from different experiments (Nelson & Barnard 1971;Baravian et al 1975;Diatta et al 1976;Adler & Piel 1991;Pérez et al 1996) and a general good agreement is found. As happened before in other comparisons, the worst agreement corresponds to the comparison with the results of Nelson & Barnard (1971) and Baravian et al (1975).…”
Section: Distance Between the Allowed And The Forbidden Componentsmentioning
confidence: 66%
“…Figure 9 shows a comparison of this parameter obtained in the simulations and in different experiments covering wide ranges of electron density and temperature. For the simulations three different cases are shown to check the influence of plasma composition or temperature in this parameter: for pure He plasma (μ = 2) at T e = T gas = 5000 and 20 000 K and for a He-H + plasma (μ = 0.5) with T e = T gas = 5000 K. A good agreement is Simulation T=5000 K, μ=0.8 T=5000 K, μ=2.0 T=20000 K, μ=2.0 Experiment Nelson 1971Baravian 1975Diatta 1976Adler 1991Pérez 1996 Fig. 9.…”
Section: Ratio Of Allowed and Forbidden Component Intensitiesmentioning
confidence: 88%
See 1 more Smart Citation
“…The observed plasma satellites (see e. g. Kunze and Griem 2G , Burrell and Kunze 2~, Cooper and Ringler 28 , C. C. Gallagher and Levine 29 , Rutgers and de Kluiver 30 , Rutgers and Kalfsbeek 31 ) can be explained in the frame of the Baranger and Mozer 32 theory. But electron plasma wave satellites have also been observed in apparently quiescent plasmas with a very low turbulence level (Ya'akobi and Bekefi 33 and Baravian et al 34 ). As these laser-produced plasmas were observed during the recombination phase it is possible that the energy was delivered by supra-thermal electrons produced by superelastic electron collisions (see e. g. Chappel, Cooper and Smith 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, global OP conservation, which is applicable for the canonical ensemble, can induce drastic changes of the CCF [15,16]. Hitherto, only a few studies have focused on the effect of a global OP constraint on the critical behavior [17][18][19][20][21]. In the present study, building on Ref.…”
Section: Introductionmentioning
confidence: 99%